Who Owns a Handgun? An Analysis of the Correlates of Handgun Ownership in Young Adulthood - Gresham, Mitchell (Crime & delinquency, 2020)
Previous research on firearms has not adequately addressed a fundamental question about handgun ownership: Why do some people own handguns while most in the United States do not? We use data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) to examine adolescent and adult correlates of handgun ownership, including socialization, victimization and fear of crime, political ideology, and societal insecurities. We also investigate the differences between "typical" owners and "atypical" owners who own more handguns. We find that socialization, victimization, conservatism, and societal insecurity all independently increase the likelihood of handgun ownership, and atypical handgun owners are more likely to be conservative and to have experienced victimization than typical owners.